Acute effects of high-intensity interval training on cognition and retinal microcirculation in experienced amateur boxers - Solianik, R.; Bruzas, V.; Mockus, P.; Vadopalas, K.; Streckis, V. (The Journal of Sports Medicine and Physical Fitness, 2021)
BACKGROUND: Limited and contradictory data are available regarding the acute effects of endurance exercises on cognition and retinal microcirculation. Thus, we aimed to evaluate the acute effects of sport-specific high-intensity interval training (HIIT) on cognition and retinal vessel diameters in experienced amateur boxers. METHODS: Eleven young (age 22.8 ± 2.9 years) men with 10.7 ± 4.8 years of boxing experience completed two sessions in random order: high-intensity intermittent punching load and passive rest. Cardiovascular response, retinal vessel diameters, and cognitive performance were evaluated at baseline, during exercise, and immediately after each session. RESULTS: Increased heart rate during intermittent punching load (p < 0.05) reaching 91.2 ± 3.7% of the maximal heart rate was observed. The HIIT improved cognitive flexibility and inhibitory control (p < 0.05), while the working memory and motor speed were not affected. Significant dilatation of temporal retinal venules (p < 0.05) was observed after the HIIT compared with the values before the HIIT, resulting in a decreased arteriolar-to-venular diameter ratio (p < 0.05). CONCLUSIONS: At the functional level, an improvement in executive function due to intermittent high-intensity punching load was observed, while at the physiological level, retinal venular dilatation was observed in experienced amateur boxers.